Development of Islamic Cultural History Teaching Module Based on Local Wisdom for Students of Madrasah Tsanawiyah - Imran, Risdayani; Muhaemin, Muhaemin; Pamessangi, Andi Arif; Rani, Hadijah (Educational Journal of Learning Technology, 2025)
This research aims to develop a teaching module of Islamic Cultural History integrated with local wisdom in Tana Luwu and test its validity and practicality in the material of Umar bin Abdul Aziz's Leadership Style for grade VII students. The research uses the Research and Development (R&D) method with the ADDIE development model. The study subjects were 35 grade VII students, with instruments like interviews, assessment sheets, and documentation. The validation results showed that the module was declared valid with a percentage of 75% of media experts, 98% of material experts, and 67% of linguists. The practicality test by the teacher resulted in a percentage of 88% (very practical category), while the test by students obtained 81% (very practical category). With these results, the integrated teaching module of local wisdom in Tana Luwu was declared valid and practical for learning Islamic Cultural History in grade VII.